2011
DOI: 10.1128/aac.01814-10
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in gidB Confer Low-Level Streptomycin Resistance in Mycobacterium tuberculosis

Abstract: The global threat posed by drug-resistant strains of Mycobacterium tuberculosis demands a greater understanding of the genetic basis and molecular mechanisms that govern how such strains develop resistance against various antituberculous drugs. In this report, we examine a new genetic basis for resistance to one of the oldest and most widely used second-line drugs employed in tuberculosis therapy, streptomycin (SM). This marker for SM resistance was first discovered on the basis of genomic data obtained from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 31 publications
(47 reference statements)
2
100
0
2
Order By: Relevance
“…Among the non-Beijing strains, the gidB C413T mutation has been found in both STR-resistant and -susceptible M. tuberculosis isolates (20,21,23). One STR-resistant isolate carried the mutation G248C, indicating that it might lead to resistance to this drug; however, other mutations in this position (G248T) have been found in STR-susceptible strains (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the non-Beijing strains, the gidB C413T mutation has been found in both STR-resistant and -susceptible M. tuberculosis isolates (20,21,23). One STR-resistant isolate carried the mutation G248C, indicating that it might lead to resistance to this drug; however, other mutations in this position (G248T) have been found in STR-susceptible strains (21).…”
Section: Resultsmentioning
confidence: 99%
“…Many missense mutations have been described in STR-susceptible strains, such as the mutation T47G (the most frequent mutation found in our study), which has been reported as being specific to the Latin American-Mediterranean (LAM) family strains (22); in fact, the 6 strains carrying this mutation in our study belong to the LAM family of strains (data not shown). The four Beijing strains carried two mutations: A276C (E92D), which has been described as an SNP specific to this family (22), and A615G; both mutations can be found in STR-susceptible strains (20). In the Beijing strains, these gidB mutations occur simultaneously with the mutation A128G in the rpsL gene, as mentioned above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of participation of the 530 loop in the decoding process being clear, the precise role of the m 7 G527 modification has remained elusive. Loss of RsmG activity confers low-level streptomycin resistance and inexplicably prompts the appearance of high-level streptomycin resistance mutations in the S12-encoding gene, rpsL (Nishimura et al 2007a,b;Okamoto et al 2007;Gregory et al 2009;Wong et al 2011). Moreover, the effects of rsmG mutations on bacterial fitness and translational accuracy have been reported as being variable, depending on the bacterial species (Nishimura et al 2007b;Okamoto et al 2007;Gregory et al 2009;Ochi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mechanisms of low-level resistance to streptomycin (MIC = 4-32 mg/L) remain largely undefined but may be attributable to changes in cell envelope permeability or diminished drug uptake (Honore and Cole 1994;Cooksey, Morlock et al 1996). More recently, it has been shown that mutations in gidB, which encodes a conserved S-adenosylmethionine-dependent 16S rRNA methyltransferase, can confer low-level resistance to streptomycin (Wong, Lee et al 2011). …”
Section: Mechanism Of Resistancementioning
confidence: 99%